"Your words matter!" Relevance of individual participation in xMOOCs. (March 2021) - Riehemann, Jens; Hellmann, Jens H; Jucks, Regina
Massive open online courses are increasingly popular. One characteristic of most massive open online courses is that they are offering educational contents to masses of different individual learners. At the same time, a particular challenge for the individual learner could be the massiveness of such courses, that is, that one is part of a large crowd of other learners. Being one of many other individuals can have negative consequences on learning activities because an individual might experience a sense of virtual crowding. The experiment described in this article investigated how course type (xMOOC vs virtual seminar) and relevance of individual participation (low vs high) impact online learners' engagement. Results showed that participants in an xMOOC condition referred to themselves and their peers to a greater extent when their participation was introduced as being highly relevant. Implications for the design of xMOOCs are discussed.